An Assessment of Non-adoption of Compost Making in Piramanthanaru Grama Niladari (GN) Division of Kilinochchi District in Sri Lanka. - Thusyanthini, R.; Peramunagama, S.S.M.; De Silve, A.G.S.D. (University of Jaffna, 2020)
Waste management authority and the Central environmental authority in Sri Lanka recorded in 2018 that, 7500 tonnes solid wastes are being generated per day in the country. However, only 3500 tonnes is being collected by local authorities and remains accumulate. This study aimed to evaluate present knowledge of the people in Piramanthanaru Grama Niladari (GN) division, of Kandauualai Divisional Secretariate (DS) in Kilinochchi, Sri Lanka on home waste management and divergent contentions for non-adoption of compost making and suggestions for future adoption. Focus group discussion (FGDs), Participatory rural appraisal techniques (Transect walks, pair wise ranking and resource map) and written test were employed for data collection. FGDs were conducted with participants who were purposively selected from Piramanthanaru GN division. Decomposition rate of home wastage, methods of compost making, application of compost and its importance were questioned. The results revealed that minority (30%) obtained approximately 50% of total marks while others scored less than 10%.The majority (75%) of households used plastics, polybags as cooking fuel which depicts ambiguity of health hazardous. E- wastes considerably accumulated at households due to absence of local authorities. Pairwise ranking showed, lack of awareness on compost application and its importance, uncertainty of compost making methods, and requirement of large quantity compost were ranked firstly, secondly and thirdly as divergent contentions for non-adoption respectively. Attention of local authorities, regular visits of relevant officers and continual training and development were suggested for future adoption. To sum up, uncertainity often causes non/poor adoption. It is clear the necessity of integrated solid waste management around the country.
Keywords: Compost.; House hold waste management.; Participatory rural appraisal.